Evaluation of the Dengue NS1 Ag Strip for Detecting Dengue Virus Antigen in Wild-Captured and Laboratory-Reared Aedes aegypti - Chaiti, Nusrat Jahan; Bashar, Kabirul; Ahmed, Sohel; Jhara, Moumita Sharmin; Haque, Md Mujammel; Apon, Farhan Chowdhury; Jahan, Neshat; Naiem, Md; Al Latif, Afsana; Mim, Tabassum Mostafa (Bangladesh Journal of Zoology, 2025)
Abstract not available Bangladesh J. Zool. 53(2): 237-244, 2025